Middle Ages Account Books (Books and Records of the Famous Italian Medici Bank and Other Trade and Banking Companies) - Даньків, Й. Я.; Остап’юк, М. Я. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The article reveals the genesis of double-entry bookkeeping in the territory of Italy on the basis of Francesco di Marco books Datini, the famous Italian house of the Medici (1395). Early treatises do not give proper characteristics of a true medieval practice of accounting, all leading commercial and banking centers comply with the rules of closing the books and balance sheet. It was established that the early treatises were unable to give a clear picture of accounting. In the Middle Ages, the Italians were on top of commerce, organization of companies, banks and accounting course. In the main factors of this growth: the company, and credit intermediation, known and others who contributed to the highest level in Europe. These include the introduction of Italian mathematician Leonardo of Pisa (Fibonacci) in the 1202 Arab figures instrumentation - "abacus" (medieval abacus). This scientist described in his book "The Book of abaca" because growth of mathematical knowledge to ensure the accuracy of accounting calculations.